PENINGKATAN SIKAP SOSIAL DAN HASIL BELAJAR IPS SD MELALUI MODEL SNOWBALL THROWING - Leny Marlina; Pargito Pargito; Darsono Darsono (Faculty of Teacher Training and Education, University of Lampung, 2015)
The objectives of this research were describing the use of model Snowball Throwing model to improve social skill in studying IPS, and to increase students achievement. The type of research was classroom action research. Data analizing consisted of validation stages, data reduction, data display and data verification. Based on the results of the data analysis and discussion, it can be concluded as follows: (1) learning with picture and picture method can increase student activity. It can be seenfrom the average percentage of students social skill increased by first cycle 69,84 to 76,88% in the second cycle and 81,02 % in the third cycle. (2) Learning by using Snowball Throwing model can increase students achievement. It can be seen from the increase in the percentage of students achievement increased by 74,19 % in the first cycle to 80,65 % in the second cycle, 87,10 in the third cycle.Tujuan dilaksanakannya penelitian ini antara lain: untuk mendeskripsikan penggunaan model Snowball Throwing meningkatkan sikap sosial dalam pembelajaran IPS, meningkatkan hasil belajar siswa dalam pembelajaran IPS. Jenis penelitian ini adalah Penelitian Tindakan Kelas. Analisis data meliputi tahapan pemvalidasian, reduksi data, menampilkan data dan verifikasi data. Berdasarkan hasil analisis data dan pembahasan diperoleh kesimpulan sebagai berikut: (1) Pembelajaran dengan model Snowball Throwing dapat meningkatkan sikap sosial siswa kelas. Hal ini dapat dilihat dari rata-rata persentase sikapsosial siswa meningkat dari siklus I sebesar 69,84% menjadi 76,88 % pada siklus II dan pada siklus III 81,02. (2) Pembelajaran menggunakan model Snowball Throwing dapat meningkatkan hasil belajar siswa. Hal ini dapat dilihat dari peningkatan persentase hasil belajar siswa meningkat dari 74,19 % pada siklus 1 menjadi 80,65 % pada siklus II, 87,10 % pada siklus III.Kata kunci: hasil belajar, model snowball throwing, sikap sosial